2020
DOI: 10.1136/bmjopen-2019-034074
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of deaths from pneumonia and tuberculosis in children in Brazil: an ecological study

Abstract: ObjectiveTo identify the risk areas of deaths due to unspecified pneumonia and tuberculosis (TB) in children, and to identify if there is a relationship between these events with higher TB incidence and social determinants.MethodsEcological study carried out in Brazil. All cases of TB or unspecified pneumonia deaths in children under 5 years of age reported between 2006 and 2016 were included and collected through Department of Informatics of the Unified Health System (Brazil’s electronic database). The Spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The overall reporting of the WHO SDOH categories is summarized in Table 1, and the geographic distribution of included articles is shown in (10), UMIC (13), LMIC ( 14), and LIC (1) Argentina (1), Bangladesh (3), Brazil (4), China (5), Colombia (1), Egypt (3), Europe (1), France (1), Ghana (1), India (5), Ireland 1). For nutrition, 38 articles reported 24 different measures reflecting nutrition, weight, height, or body mass index.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall reporting of the WHO SDOH categories is summarized in Table 1, and the geographic distribution of included articles is shown in (10), UMIC (13), LMIC ( 14), and LIC (1) Argentina (1), Bangladesh (3), Brazil (4), China (5), Colombia (1), Egypt (3), Europe (1), France (1), Ghana (1), India (5), Ireland 1). For nutrition, 38 articles reported 24 different measures reflecting nutrition, weight, height, or body mass index.…”
Section: Resultsmentioning
confidence: 99%
“…Given that numerous studies have documented the importance of SDOH on outcomes of critically ill children across the globe (2,3,5,8,20,23,24,70,(73)(74)(75), researchers have a collective responsibility to design studies to include SDOH variables so as not to perpetuate implicit and explicit biases regarding minoritized groups and to ensure consistent and standardized collection and reporting of these variables when conducting future studies in pediatric sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that governments take responsibility for ensuring universal health coverage as a key element in achieving global goals [5,41]. In one study, primary care coverage was inversely associated with TB mortality in children [9]. Ross et al (2018) concluded that greater population coverage of Family Health Program teams (PHC) was associated with lower TB and HIV mortality [11].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Simple policies can be delivered effectively in primary healthcare (PHC) to prevent TB in individuals at high risk [8,9]. A consistent supply of primary care services can lead to improved access, better contact tracing, shorter waiting times for patients [10], and enhanced TB case detection [9].…”
Section: Introductionmentioning
confidence: 99%